2013
DOI: 10.1021/ol4015738
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Calothrixins and Its Analogs Using FeCl3-Mediated Domino Reaction Protocol

Abstract: A novel one pot synthesis of calothrixin B and its analogs is achieved involving an FeCl3-mediated domino reaction of enamines in dry DMF at reflux. Alternatively, the enamines upon interaction with CuBr2 in DMF at reflux led to the formation of 1-phenylsulfony-2-(2'-nitroaryl)-4-hydroxycarbazole-3-carbaldehydes in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Treating 290 with FeCl 3 in boiling DMF provided 285 through electrocyclization/oxidation/reduction of the nitro group/cyclization cascade (Scheme 72). 113 The cycloaddition reaction of furoindole 279 with 3,4-pyridyne, generated from 3-bromopyridine in situ, produced pyridocarbazole 280, which was then converted to ellipticine (278) (Scheme 73). 114 …”
Section: Indole Phytoalexinsmentioning
confidence: 99%
“…Treating 290 with FeCl 3 in boiling DMF provided 285 through electrocyclization/oxidation/reduction of the nitro group/cyclization cascade (Scheme 72). 113 The cycloaddition reaction of furoindole 279 with 3,4-pyridyne, generated from 3-bromopyridine in situ, produced pyridocarbazole 280, which was then converted to ellipticine (278) (Scheme 73). 114 …”
Section: Indole Phytoalexinsmentioning
confidence: 99%
“…The reaction of 4,5-dichloro-2-nitrobenzaldehyde (1h, [24] 0.5 g, 2.27 mmol) with triethyl phosphite (0.75 g, 4.54 mmol) in the presence of ZnBr 2 (0.05 g, 0.22 mmol) at room temperature for 10 min followed by workup using general procedure I afforded trans-epoxide 2h …”
Section: (2s*3s*)-23-bis(45-dichloro-2-nitrophenyl)oxirane (2h)mentioning
confidence: 99%
“…As part of our studies of Lewis‐acid‐mediated domino reactions,16 we recently reported a synthesis of calothrixin B and its analogs involving an FeCl 3 ‐mediated domino reaction of enamines 17. Prior to this report on calothrixin B, syntheses of quino[4,3‐ b ]carbazole18 and indolo[2,3‐ a ]carbazole19 using a thermal electrocyclization strategy were also achieved in our lab.…”
Section: Resultsmentioning
confidence: 99%
“…We started our synthesis of calothrixin B from the known 1‐phenylsulfonyl‐2‐nitrophenylvinylindole 7 17. α‐Bromination of 2‐nitroaryl‐3‐acetylindole 7 using phenyltrimethylammonium tribromide (PTT)20 in dry THF gave bromo compound 8 .…”
Section: Resultsmentioning
confidence: 99%